Long-term reduced functional capacity and quality of life in hospitalized COVID-19 patients - da Silveira, Anderson Donelli; Scolari, Fernando Luis; Saadi, Marina Petersen; Brahmbhatt, Darshan H.; Milani, Mauricio; Milani, Juliana Goulart Prata Oliveira; Junior, Gerson Cipriano; Sartor, Ivaine Tais Sauthier; Zavaglia, Gabriela Oliveira; Tonini, Maiko Luis; da Costa, Marcela Santos Correa; Scotta, Marcelo Comerlato; et al. (Frontiers in Medicine, 2024)
Background: Persistent symptoms and exercise intolerance have been reported after COVID-19, even months after the acute disease. Although, the long-term impact on exercise capacity and health-related quality of life (HRQoL) is still unclear.Question: To assess the long-term functional capacity and HRQoL in patients hospitalized due to COVID-19. Study Design and Methods: This is a prospective cohort study, conducted at two centers in Brazil, that included post-discharge COVID-19 patients and paired controls. The cohort was paired by age, sex, body mass index and comorbidities, using propensity score matching in a 1:3 ratio. Patients were eligible if signs or symptoms suggestive of COVID-19 and pulmonary involvement on chest computed tomography. All patients underwent cardiopulmonary exercise testing (CPET) and a HRQoL questionnaire (SF-36) six months after the COVID-19. The main outcome was the percentage of predicted peak oxygen consumption (ppVO2). Secondary outcomes included other CPET measures and HRQoL. Results: The study sample comprised 47 post-discharge COVID-19 patients and 141 healthy controls. The mean age of COVID-19 patients was 54 + 14 years, with 19 (40%) females, and a mean body mass index of 31 kg/m 2 (SD, 6). The median followup was 7 months (IQR, 6.5-8.0) after hospital discharge. PpVO2 in COVID-19 patients was lower than in controls (83% vs. 95%; P=0.002) with an effect size of 0.38 ([95%CI], 0.04-0.70). Mean peak VO2 (22 vs. 25 ml/kg/min; p=0.04) and OUES (2,122 vs. 2,380; p=0.027) were also reduced in the COVID-19 patients in comparison to controls. Dysfunctional breathing (DB) was present in 51%. HRQoL was significantly reduced in post COVID patients and positively correlated to peak exercise capacity. Interpretation: Hospitalized COVID-19 patients presented, 7 months after discharge, with a reduction in functional capacity and HRQoL when compared to historical controls. HRQoL were reduced and correlated with the reduced peak VO2 in our population. Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Formatado: Inglês (Americano)